Impacts of host phylogeny, diet, and geography on the gut microbiome of rodents - Sufia Akter Neha; John D. Hanson; Jeremy E. Wilkinson; Robert D. Bradley; Caleb D. Phillips (PLoS ONE, 2025)
Mammalian gut microbial communities are thought to play a variety of important roles in health and fitness, including digestion, metabolism, nutrition, immune response, behavior, and pathogen protection. Gut microbiota diversity among hosts is strongly shaped by diet as well as phylogenetic relationships among hosts. Although various host factors may influence microbial community structure, the relative contribution may vary depending on several variables, such as taxonomic scales of the species studied, dietary patterns, geographic location, and gut physiology. The present study focused on 12 species of rodents representing 3 rodent families and 3 dietary guilds (herbivores, granivores, and omnivores) to evaluate the influence of host phylogeny, dietary guild and geography on microbial diversity and community composition. Colon samples were examined from rodents that were collected from 7 different localities in Texas and Oklahoma which were characterized using 16S rRNA gene amplicon sequencing targeting the V1-V3 variable regions. The microbiota of colon samples was largely dominated by the family Porphyromonadaceae (Parabacteriodes, Coprobacter) and herbivorous hosts harbored richer gut microbial communities than granivores and omnivores. Differential abundance analysis showed significant trends in the abundance of several bacterial families when comparing herbivores and granivores to omnivores, however, there were no significant differences observed between herbivores and granivores. The gut microbiotas displayed patterns consistent with phylosymbiosis as host phylogeny explained more variation in gut microbiotas (34%) than host dietary guilds (10%), and geography (3%). Overall, results indicate that among this rodent assemblage, evolutionary relatedness is the major determinant of microbiome compositional variation, but diet and to a lesser extent geographic provenance are also influential.